Sphenopalatine Ganglion Stimulation Upregulates Transport of Temozolomide across the Blood-Brain Barrier - Thana N. Theofanis; Ankit K. Rochani; Richard F. Schmidt; Michael J. Lang; Geoffrey P. Stricsek; Robert H. Rosenwasser; Ashwini D. Sharan; Gagan Kaushal; Lorraine Iacovitti (MDPI AG, 2020)
Sphenopalatine ganglion (SPG) stimulation has been shown to reversibly alter blood-brain barrier (BBB) permeability. It is widely used for the treatment of cluster headaches in Europe and is well tolerated in humans. The therapeutic potential for SPG stimulation in other central nervous system (CNS) diseases has yet to be explored. Glioblastoma Multiforme (GBM) remains one of the most difficult primary CNS neoplasms to treat, with an average survival of approximately 18 months at the time of diagnosis. Since 2004, the gold standard of treatment for GBM in the United States includes surgery followed by treatment with temozolomide (TMZ) and radiation. We sought to determine if SPG stimulation could increase chemotherapy concentrations in rodent brains with an intact BBB. Here, we show a statistically significant (p = 0.0006), five-fold upregulation of TMZ crossing the BBB and reaching brain parenchyma in rats receiving low-frequency (LF, 10 Hz) SPG stimulation. All the measurements were performed using a highly sensitive liquid chromatography mass spectrometry (LCMS) method that was developed for quantitation of TMZ in plasma and brain tissue. Our treatment paradigm shows novel delivery route by which we could more effectively and safely deliver TMZ in a targeted manner, to minimize systemic toxicity and maximize action at the target tissue.